What activities are actually engaged by school leaders in leadership for learning? Literature review - Bos, Sylvie; Chaliès, Sébastien (Swiss Journal of Educational Research, 2019)
This article reports on the literature on the day-to-day activities of school leaders in exercising leadership for learning. It helps to highlight that while the «school leadership effect» on the improvement of student success appears to be well studied, it remains little discussed in terms of actually deployed daily activities in schools. On the basis of the description of the main activities studied, such as those relating to school mission, mobilization and training of teachers, influence on pedagogical practices, or strategic use of school’s structure and organization, the article opens new avenues of work.